REPRESENTASI PEREMPUAN DALAM IKLAN PRODUK KECANTIKAN “BODY SERUM SCARLETT” DENGAN PENDEKATAN TEORI SARA MILLS - Anik Sulistiyowati; Asropah (STKIP Subang, 2025)
This study aims to analyze the representation of women in Body Serum Scarlett beauty product advertisements using Sara Mills’s Critical Discourse Analysis (CDA) approach. This approach focuses on how subject-object positions are constructed and how audiences are ideologically positioned. The findings show that the Body Serum Scarlett advertisement constructs an ideal concept of beauty through both narration and visual presentation.